Powder granulation and method for producing powder granulation

The powder granulated product, composed of true spherical polymer fine particles, transparent polymer powder, and a specific binder, addresses the challenges of uniformity and productivity in masterbatch production, achieving excellent optical and handling properties while reducing dust explosion risks.

JP7671906B1Active Publication Date: 2025-05-02NAGASE & CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024146900
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-05-02
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The production of masterbatches containing fine spherical polymer particles faces challenges such as low rolling resistance, difficulty in controlling quantitative flow, and low bulk density, which affect uniformity, productivity, and dust control.

Method used

A powder granulated product comprising true spherical polymer fine particles, transparent polymer powder, and a binder with hydrophilic and hydrophobic groups, where the spherical polymer fine particles are 10-97 parts by mass, the transparent polymer powder is 1-88 parts by mass, and the binder is 2-30 parts by mass, is used. This product is produced through a process involving mixing, granulation, and heating, allowing for improved handling and optical properties.

Benefits of technology

The powder granulated product achieves excellent optical properties, compositional uniformity, granulation stability, dispersibility in thermoplastic resins, color tone maintenance, and enhanced productivity, while reducing the risk of dust explosions and improving handling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671906000001_ABST
    Figure 0007671906000001_ABST
Patent Text Reader

Abstract

The present invention provides a powder granulation product containing spherical polymer fine particles, which is excellent in optical properties, physical properties and productivity. [Solution] The powder granule according to an embodiment of the present invention comprises spherical polymer microparticles (A), transparent polymer powder (B), and a binder (C), the content of the spherical polymer microparticles (A) being 10 parts by mass to 97 parts by mass relative to 100 parts by mass of the powder granule, the content of the transparent polymer powder (B) being 1 part by mass to 88 parts by mass relative to 100 parts by mass of the powder granule, and the content of the binder (C) being 2 parts by mass to 30 parts by mass (dry mass) relative to 100 parts by mass of the powder granule, the binder (C) comprising an aqueous polymer having a hydrophilic group and a hydrophobic group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powder granulated product and a method for producing the powder granulated product. [Background technology]

[0002] In the production of polymers (e.g., thermoplastic polymers), a powdered polymer may be obtained due in part to the method, and spherical polymer particles are known as one form of the powdered polymer. Powdered polymers are generally blended with thermoplastic resins by melt kneading, but it is desirable to make them into a master batch of an appropriate concentration in order to improve the handling property, uniformity of concentration, and productivity. From another viewpoint, it is desirable to make them into a master batch from the viewpoint of improving the dusty working environment and avoiding dust explosions. In general, a master batch with a controlled composition ratio can be obtained by quantitatively feeding the polymer to a melt kneading device such as an extruder through a screw-type gravimetric feeder.

[0003] However, when spherical polymer particles are used, the rolling resistance of the particles is extremely small, so that it is difficult to control the flow rate of the particles by the screw of a gravimetric feeder, and it is difficult to continuously supply the particles stably with high accuracy, which is one of the reasons why the desired concentration uniformity cannot be obtained. In addition, the bulk density of the spherical polymer particles is small, so that the flow rate does not increase, which may cause problems such as limiting the production speed of the master batch and the increase in concentration.

[0004] The spherical polymer fine particles are sometimes blended with a transparent resin and used as a light diffusing agent. A light diffusing resin composition containing the spherical polymer fine particles as a light diffusing agent is required to have both light diffusing property and light transmittance. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2023-011323 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a powder granulation product containing true spherical polymer microparticles, which has excellent optical properties, compositional uniformity, granulation product stability, dispersibility in thermoplastic resins, color tone retention, and productivity. [Means for solving the problem]

[0007] 1. A powder granulation product according to an embodiment of the present invention comprises spherical polymer microparticles (A), transparent polymer powder (B), and a binder (C), the content of the spherical polymer microparticles (A) being 10 parts by mass to 97 parts by mass relative to 100 parts by mass of the powder granulation product, the content of the transparent polymer powder (B) being 1 part by mass to 88 parts by mass relative to 100 parts by mass of the powder granulation product, and the content of the binder (C) being 2 parts by mass to 30 parts by mass (dry mass) relative to 100 parts by mass of the powder granulation product, the binder (C) comprising an aqueous polymer, the aqueous polymer having a hydrophilic group and a hydrophobic group. 2. In the powder granulation product described in 1 above, the material constituting the spherical polymer microparticles (A) may be one or more selected from the group consisting of crosslinked acrylic resins, crosslinked styrene resins, crosslinked acrylic-styrene resins, crosslinked silicone resins, crosslinked silicone-acrylic resins, melamine resins and benzoguanamine resins. 3. In the powder granulated product according to 1 or 2 above, the ratio (b / a) of the minor axis b of the spherical polymer fine particles (A) to the major axis a of the spherical polymer fine particles (A) may be 0.9 or more. 4. In the powder granulated product according to any one of the above 1 to 3, the median diameter (D50) of the spherical polymer fine particles (A) may be 0.1 μm to 300 μm. 5. In the powder granulated product according to any one of the above 1 to 4, the spherical polymer fine particles (A) may have a bulk density of 0.05 kg / L to 1.0 kg / L. 6. In the powder granulated product according to any one of the above items 1 to 5, the spherical polymer fine particles (A) may have a refractive index of 1.40 to 1.70. 7. In the powder granule described in any one of 1 to 6 above, the material constituting the transparent polymer powder (B) may be one or more selected from the group consisting of styrene-based resins, acrylic-based resins, styrene-methacrylate-based resins, polycarbonate-based resins, polyester-based resins, polyurethane-based resins, petroleum resins, terpene-based resins, and alicyclic polyolefin-based resins. 8. In the powder granulated product according to any one of 1 to 7 above, the transparent polymer powder (B) may have a median diameter (D50) of 1 μm to 3000 μm. 9. In the powder granulated product according to any one of the above items 1 to 8, the refractive index of the transparent polymer powder (B) may be 1.45 to 1.65. 10. In the powder granulated product according to any one of 1 to 9 above, the transparent polymer powder (B) may have a bulk density of 0.10 kg / L to 0.70 kg / L. 11. In the powder granulated product according to any one of 1 to 10 above, the median diameter (D50) of the aqueous polymer may be 0.5 μm or less. 12. In the powder granulated product according to any one of 1 to 11 above, the aqueous polymer may be one or more types selected from the group consisting of acrylic resins, polyester resins, and polyurethane resins. 13. The powder granulated product according to any one of 1 to 12 above may have a breaking stress of 0.3 kg or more when measured using a Kiya hardness tester. 14. The powder granulated product according to any one of 1 to 13 above may have a bulk density of 0.3 kg / L to 1.0 kg / L. 15. The powder granulated product according to any one of 1 to 14 above may have a median diameter (D50) of 1 mm to 10 mm. 16. The powder granulated product according to any one of 1 to 5 above may have a substantially cylindrical or substantially prismatic shape. 17. The method for producing the powder granulation product according to an embodiment of the present invention includes a mixing step of mixing spherical polymer fine particles (A), transparent polymer powder (B), and a binder (C) to obtain a powder mixture; The method includes a granulation step of compressing and granulating the powder mixture to obtain a powder granulated product precursor; and a heating step of heating the powder granulated product precursor. 18. In the method for producing a powder granulated product described in 17 above, in the granulation step, the compression granulation method may be a disk pelletizer method. 19. In the method for producing a powder granulation product described in 17 or 18 above, the binder (C) may contain an aqueous polymer, and the mixing step may include adding an aqueous solution containing the aqueous polymer or an aqueous dispersion containing the aqueous polymer. 20. The powder granules according to the embodiment of the present invention may be used as a raw material for a compound containing a thermoplastic resin, or as a molding material. 21. The powder granulated material described in 20 above may be used as a raw material for a thermoplastic resin compound containing, as a thermoplastic resin, one or more selected from the group consisting of styrene-based resins, acrylic-based resins, styrene-methacrylate-based resins, polycarbonate-based resins, and alicyclic polyolefin-based resins. 22. In the use of the powder granules according to 20 or 21 above, the ratio (nP / nB) of the refractive index nB of the transparent polymer powder (B) to the refractive index nP of the thermoplastic resin may be 0.8 to 1.2. Effect of the Invention

[0008] According to the present invention, it is possible to provide a powder granulation product containing spherical polymer microparticles, which has excellent optical properties, compositional uniformity, granulation stability, dispersibility in thermoplastic resins, color tone retention, and productivity. [Brief description of the drawings]

[0009] [Figure 1]1 is a photograph showing the appearance of the granulated product of Example 1. [Diagram 2] 1 is an image of a cross section of the powder granulated product obtained in Example 1 observed with a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A. Overview of powder granulation The powder granulated product according to the embodiment of the present invention includes spherical polymer particles (A), transparent polymer powder (B), and binder (C). The spherical polymer particles (A), transparent polymer powder (B), and binder (C) can be distinguished by their shapes (typically, shapes by cross-sectional observation). The spherical polymer particles (A) have a median diameter (D50) of 0.1 μm or more and are spherical. The transparent polymer powder (B) refers to a polymer that has a median diameter (D50) of 0.1 μm or more, is non-spherical, and is transparent. In this specification, "spherical" means a shape in which the ratio (b / a) of the minor axis b to the major axis a is 0.9 or more, and "non-spherical" is a general term for shapes other than "spherical". "Transparent" means a state in which light is efficiently transmitted without being reflected, and a haze (%) value according to JISK7136 for plastics is less than 4% for a sample with a thickness of 1 mm. The binder (C) refers to a component that does not have a granular form in the powder granulation product. In one embodiment, the binder (C) is present between components (A) and (A), between components (B) and (B), or between components (A) and (B), and is present to bind the components together and stabilize the shape of the powder granulation product.

[0011] In one embodiment, the content of the spherical polymer fine particles (A) is 10 parts by mass to 97 parts by mass relative to 100 parts by mass of the powder granulation product. The content of the transparent polymer powder (B) is 1 part by mass to 88 parts by mass relative to 100 parts by mass of the powder granulation product. The content of the binder (C) is 2 parts by mass to 30 parts by mass (dry mass) relative to 100 parts by mass of the powder granulation product. In one embodiment, the total content of the spherical polymer fine particles (A), the transparent polymer powder (B) and the binder (C) is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, even more preferably 90 parts by mass or more, and even more preferably 95 parts by mass or more relative to 100 parts by mass of the powder granulation product. In one embodiment, the total content of the spherical polymer microparticles (A), the transparent polymer powder (B) and the binder (C) is 100 parts by mass relative to 100 parts by mass of the powder granule (i.e., the powder granule is composed of the three components, component (A), component (B) and component (C)).

[0012] In one embodiment, the powder granulation product can be obtained by processing a mixture containing the spherical polymer fine particles (A), the transparent polymer powder (B), and the binder (C) (for example, the binder can be blended as an aqueous solution or aqueous dispersion) by any appropriate method. In one embodiment, the powder granulation product is produced by a semi-wet granulation method.

[0013] In one embodiment, the powder granulation product is composed of spherical polymer fine particles (A) and transparent polymer powder (B) bound together by the action of a binder (C). By forming the powder granulation product from these components, a powder granulation product can be obtained as a compressed granulation product. The powder granulation product is excellent in quality stability (shape stability, uniformity of hardness, low fine powder mixing). In addition, the powder granulation product is excellent in optical properties, composition uniformity, granulation product stability, dispersibility in thermoplastic resins, color tone retention, and productivity. In addition, the powder granulation product can be produced without melting the spherical polymer fine particles (A), which is advantageous in that there is a wide range of selection for the type of spherical polymer fine particles (A) used as a raw material. In addition, since the granulation product is obtained without melting the spherical polymer fine particles (A), thermal deterioration (e.g., yellowing) of the spherical polymer fine particles (A) can be prevented.

[0014] The powder granule contains the transparent polymer powder (B), so that the range of the content ratio of the spherical polymer fine particles (A) in the powder granule can be preferably adjusted. In one embodiment, since the proper concentration of the spherical polymer fine particles (A) in the powder granule can be freely controlled, for example, as a light diffusing agent master batch, a powder granule having excellent handleability and easy to control the light diffusing agent concentration in the final light diffusing resin composition can be provided. In addition, by preferably selecting the refractive index of the transparent polymer powder (B), the optical properties (balance of light diffusivity and transmittance) of the resin composition obtained by using the powder granule as a light diffusing agent master batch can be improved.

[0015] The binder (C) includes an aqueous polymer. The aqueous polymer preferably has a hydrophilic group and a hydrophobic group. According to an embodiment of the present invention, by using a specific binder (C), the amount of the binder (C) can be reduced, and as a result, a powder granulated product with excellent dispersibility and little coloring can be obtained. In addition, by using the binder (C), in addition to being able to produce a powder granulated product with excellent efficiency, a powder granulated product with excellent handleability such as quality stability (shape stability and composition uniformity), low fineness, and sufficient granulated product breaking strength can be obtained.

[0016] The powder granulated material can be added to a resin composition in various plasticizing melt processes, including melt compounding (melt kneading) of the resin composition.

[0017] If the powder granules are added during plasticization melt processing (typically, melt kneading) of a resin composition, the productivity of the melt kneading process can be improved. Specifically, since the powder granules have a remarkably excellent charging stability into an extruder or other device, the use of the powder granules can dramatically improve the productivity (compound processing speed per hour) while efficiently dispersing the spherical polymer fine particle powder (A) into the resin composition. In addition, the pollution of the working environment caused by dust can be significantly improved, the risk of dust explosion can be greatly reduced, and the time required for cleaning equipment changeover can be greatly reduced. The powder granules can also be directly charged into various resin molding machines such as injection molding and extrusion molding to obtain molded products. In this case, the process of "melt kneading pelletization" can be omitted, so that the amount of carbon dioxide generated in the total production process can be greatly reduced compared to the conventional method (a resin product processing method including a melt kneading pellet process).

[0018] The powder granules can be used in fields where spherical polymer microparticles are used, such as cosmetics, paints, resin molded products, and building materials, for the purpose of improving light diffusion, concealment, coatability, and texture. In one embodiment, a mixture (resin composition) of any appropriate thermoplastic resin (hereinafter referred to as the thermoplastic resin to which the powder granules are applied) and the powder granules is provided. The mixture can be used in the above applications. In one embodiment, the powder granules can be preferably used as a master batch when producing a resin composition having light diffusion properties.

[0019] The powder granulated product may have any suitable shape. Typically, the powder granulated product is cylindrical (pellet-like), and preferably has a substantially cylindrical or substantially prismatic shape.

[0020] When the powder granulated product is cylindrical (preferably substantially cylindrical or substantially prismatic), the diameter of the powder granulated product is, for example, 1 mm to 10 mm, preferably 2 mm to 8 mm, more preferably 2 mm to 6 mm, even more preferably 2.5 mm to 5 mm, and particularly preferably 2.8 mm to 3.5 mm. The length (height) of the powder granulated product is, for example, 1 mm to 10 mm, preferably 2 mm to 8 mm, more preferably 2 mm to 7 mm, even more preferably 2.5 mm to 6 mm, and particularly preferably 2.8 mm to 5.5 mm. The median diameter (D50, volume basis) of the powder granulated product is preferably in the range of 1 mm to 10 mm. With such a shape, a powder granulated product that is easy to handle can be obtained. In particular, when the powder granulated product is mixed with a thermoplastic resin, separation from the raw thermoplastic resin during production can be reduced, and the handling property can be improved and the composition uniformity can be increased. The diameter of the powder granulated product can be adjusted by the diameter of the die hole of the disc plate during granulation, and the length can be adjusted by the distance between the disc plate and the cutter. The distance can be any appropriate distance depending on the type of powdered thermoplastic polymer, etc. The distance between the disc plate and the cutter is, for example, 1 mm to 30 mm, more preferably 2 mm to 20 mm, and even more preferably 3 mm to 10 mm. In this specification, the median diameter is based on volume.

[0021] The breaking stress of the powder granulation product in the Kiya hardness tester is preferably 0.3 kg or more, more preferably 0.5 kg or more, even more preferably 1.0 kg or more, even more preferably 5.0 kg or more, even more preferably 7.0 kg or more, and particularly preferably 10 kg or more. The upper limit may exceed the measurement limit of the Kiya hardness tester (the measurement limit of Shiro Sangyo's product name "WPF1600-B" is 10 kg). Within this range, a powder granulation product having excellent handling properties and melt processability can be obtained. Here, the breaking strength refers to the average breaking stress (breaking load) measured by crushing the powder granulation product through a pressure attachment in a direction perpendicular to the longitudinal direction (extrusion direction) of the powder granulation product for 20 grains or more (preferably 25 grains or more). The diameter of the pressure surface of the pressure attachment of the Kiya hardness tester is, for example, 5 mm.

[0022] The bulk density of the powder granulation product may be any appropriate bulk density depending on the type of powdered thermoplastic polymer. The bulk density of the powder granulation product is preferably 0.3 kg / L to 1.0 kg / L, more preferably 0.5 kg / L to 0.9 kg / L. In one embodiment, the bulk density of the powder granulation product is 0.3 kg / L to 0.8 kg / L. By increasing the bulk density, the supply speed and supply stability of the powder granulation product to various processing machines are improved. The bulk density is calculated by allowing the powder granulation product to fall naturally into a basin (volume 1 L) until it is filled to the brim, and measuring the mass of the powder granulation product (unit: kg / L).

[0023] The moisture content of the powder granulation product may be any suitable moisture content. The moisture content of the powder granulation product is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, particularly preferably 1% by mass or less, and most preferably 0.5% by mass or less. The moisture content of the powder granulation product is measured using an infrared moisture meter.

[0024] A-1. Spherical polymer particles (A) The spherical polymer particles (A) can be used, for example, in cosmetics, paints, optical applications, resins, building materials, etc. The functions thereof include light diffusibility, concealment, coatability, and texture imparting properties.

[0025] As described above, in this specification, "true spherical" refers to a shape in which the ratio (b / a) of the minor axis b to the major axis a of the particle is 0.9 or more. The above b / a is preferably 0.92 or more, and more preferably 0.95 or more. If it is within such a range, the above functions can be preferably exhibited. The major axis a and the minor axis b are the number averages of 50 or more (preferably 100 or more) particles observed with a scanning electron microscope (SEM).

[0026] As described above, the content of the spherical polymer microparticles (A) is 10 to 97 parts by mass relative to 100 parts by mass of the powder granulation product. The content of the spherical polymer microparticles (A) is preferably 15 to 95 parts by mass, more preferably 20 to 90 parts by mass, and even more preferably 30 to 80 parts by mass relative to 100 parts by mass of the powder granulation product. Within such a range, a good powder granulation product excellent in granulation stability, dispersibility in thermoplastic resin, and breaking strength can be obtained. In addition, when blended with a thermoplastic resin, good dispersibility of the spherical polymer microparticles (A) in the resin and economical advantage as a high-concentration master batch can be obtained.

[0027] The spherical polymer particles (A) may be made of any suitable material. Typically, the spherical polymer particles (A) may be made of an organic polymer. Examples of materials constituting the spherical polymer particles (A) include acrylic resins, styrene resins, acrylic-styrene resins, silicone resins, silicone-acrylic resins, melamine resins, benzoguanamine microparticles, polyamide microparticles, polyurethane microparticles, and biodegradable resin microparticles (polyhydroxyalkanoate (PHA), polylactic acid (PLA), polycaprolactam (PCL), polybutylene succinate (PBS), acetyl cellulose (TAC), and the like). The resin may be a crosslinked resin. The resin constituting the spherical polymer particles (A) may be one type or two or more types.

[0028] Preferably, the spherical polymer particles (A) are composed of a crosslinked resin. In one embodiment, the material constituting the spherical polymer particles (A) is one or more selected from the group consisting of crosslinked acrylic resins, crosslinked styrene resins, crosslinked acrylic-styrene resins, crosslinked silicone resins, crosslinked silicone-acrylic resins, melamine resins, and benzoguanamine resins. More preferably, the material is one or more selected from the group consisting of crosslinked acrylic resins, crosslinked styrene resins, crosslinked acrylic-styrene resins, crosslinked silicone resins, and crosslinked silicone-acrylic resins.

[0029] The refractive index of the spherical polymer particles (A) is, for example, 1.40 to 1.70, and preferably 1.42 to 1.70. In one embodiment, the refractive index of the spherical polymer particles (A) can be appropriately selected in consideration of the refractive index of the thermoplastic resin to which the powder granulation product is applied, for the purpose of obtaining a light diffusing function. For example, when the thermoplastic resin to which the powder granulation product is applied is polycarbonate (refractive index 1.57 to 1.59), styrene-based resin (refractive index 1.58 to 1.60), etc., the spherical polymer particles (A) can be preferably selected from crosslinked acrylic resins, crosslinked acrylic-styrene resins, crosslinked silicone resins, or crosslinked silicone-acrylic resins having a refractive index of 1.49 to 1.55. Furthermore, when the transparent thermoplastic resin to which the powder granules are applied is an acrylic resin (refractive index 1.49), a cellulose acetate resin (refractive index 1.46 to 1.50), or the like, a crosslinked silicone resin or crosslinked silicone-acrylic resin having a refractive index of 1.41 to 1.45, or a crosslinked acrylic-styrene resin having a refractive index of 1.55 to 1.58 can be preferably selected as the spherical polymer microparticles (A).

[0030] The bulk density of the spherical polymer particles (A) is preferably 0.05 kg / L to 1.0 kg / L, more preferably 0.1 kg / L to 0.8 kg / L, and more preferably 0.2 kg / L to 0.6 kg / L. When the bulk density of the spherical polymer particles (A) is within this range, granulation is easy.

[0031] The median diameter (D50) of the spherical polymer microparticles (A) is preferably 0.1 μm to 300 μm, more preferably 0.5 μm to 200 μm, even more preferably 0.8 μm to 100 μm, particularly preferably 1 μm to 50 μm, and most preferably 2 μm to 20 μm. Within such a range, a powder granulated product having excellent light diffusion function can be obtained. The median diameter (D50) of the spherical polymer microparticles (A) can be measured by a laser diffraction method for the primary particles of the particles.

[0032] The spherical polymer microparticles (A) may be commercially available products, and examples thereof include "Ganzpearl (product name)" manufactured by Aica Kogyo Co., Ltd., "Techpolymer (product name)" manufactured by Sekisui Chemical Co., Ltd., "Eposter (product name)" and "Soliostar (product name)" manufactured by Nippon Shokubai Co., Ltd., "Tospearl (product name)" manufactured by Momentive Performance Materials, Inc., "KMP Series (product name)" manufactured by Shin-Etsu Polymer Co., Ltd., "Art Pearl (product name)" manufactured by Negami Chemical Industries, Ltd., and "Trepearl (product name)" manufactured by Toray Industries, Inc.

[0033] A-2. Transparent polymer powder (B) The addition of the transparent polymer powder (B) makes it possible to adjust the concentration of the spherical polymer microparticles (A). The addition of the transparent polymer powder (B) is also advantageous in improving the dispersibility of the spherical polymer microparticles (A) in the thermoplastic resin. In addition, in the compression granulation process of the powder granulation product, the addition of the transparent polymer powder (B) improves the fluidity of the powder raw material and its penetration into the die, and can also have the effect of improving the granulation speed and processing stability, as well as contributing to improving the breaking strength of the powder granulation product.

[0034] The softening temperature of the transparent polymer powder (B) is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. When the softening temperature is 50°C or higher, stable continuous productivity of powder granulation can be obtained at a high granulation rate. The "softening temperature" is the temperature at which the polymer softens substantially in response to an external stress, either the melting point or the glass transition temperature, and can be measured by a differential scanning calorimeter (DSC). In one embodiment, in the above DSC measurement, when an endothermic or exothermic peak is observed, the softening temperature corresponds to the melting point, and when only discontinuity in the baseline is observed, the softening temperature corresponds to the glass transition temperature. When both the "melting point" and the "glass transition temperature" are observed, the "melting point" is regarded as the softening temperature.

[0035] As described above, the content of the transparent polymer powder (B) is 1 to 88 parts by mass relative to 100 parts by mass of the powder granules. The content of the transparent polymer powder (B) is preferably 2 to 85 parts by mass, more preferably 3 to 80 parts by mass, even more preferably 5 to 75 parts by mass, and particularly preferably 8 to 70 parts by mass relative to 100 parts by mass of the powder granules. The amount of the transparent polymer powder (B) added can be appropriately selected in consideration of the dispersibility of the spherical polymer fine particles (A) in the resin when blended with a thermoplastic resin, and the economical advantage as a master batch.

[0036] In one embodiment, the transparent polymer powder (B) is preferably transparent and optically isotropic. The refractive index of the transparent polymer powder (B) can be determined depending on the thermoplastic resin to which the powder granule is applied. The refractive index of the transparent polymer powder (B) is, for example, 1.45 to 1.65, and preferably 1.47 to 1.60.

[0037] The transparent polymer powder (B) is preferably amorphous or nearly amorphous. Here, "amorphous" means that no endothermic peak of crystalline melting is observed in differential scanning calorimetry (DSC) measurement (heat rise: 10°C / min).

[0038] The transparent polymer powder (B) is in powder form. It may be a powder resin obtained through the manufacturing process, that is, a powder due to the manufacturing process, or may be a powder resin obtained by pulverizing a non-powder resin such as a pellet-shaped resin, a lump-shaped resin, or a resin molding. The pulverized powder resin can be obtained by cooling a molded product, a pellet, a sprue, a runner, etc. generated in injection molding at room temperature or, if necessary, using dry ice or liquid nitrogen, and then using a pulverizer (for example, Dalton Co., Ltd., product names "Nea Mill, Sylphid Mill, Atomizer, Impact Mill, etc.").

[0039] The transparent polymer powder (B) is preferably amorphous and has a structure with a large surface area per unit mass. For example, a powdered resin obtained by pulverization may be preferable. With such a shape, the binding effect of the binder (C) is preferably exerted, and the breaking strength of the powder granules can be increased.

[0040] Examples of materials constituting the transparent polymer powder (B) include styrene-based resins, acrylic-based resins, styrene-methacrylate-based resins, polycarbonate-based resins, polyester-based resins, polyurethane-based resins, petroleum resins, terpene-based resins, and alicyclic polyolefin-based resins. These resins may be used alone or in combination of two or more. These resins are advantageous in that they have good optical compatibility with the thermoplastic resin to which the powder granules are applied when the powder granules are used as a light diffusing agent.

[0041] The transparent polymer powder (B) may have any suitable particle size as long as the effects of the present invention are obtained. The median diameter (D50) of the transparent polymer powder (B) is preferably 1 μm to 3000 μm, more preferably 5 μm to 1000 μm, still more preferably 10 μm to 800 μm, still more preferably 20 μm to 600 μm, still more preferably 50 μm to 400 μm, and particularly preferably 100 μm to 300 μm.

[0042] The bulk density of the transparent polymer powder (B) may be any appropriate bulk density as long as the effects of the present invention are obtained. The bulk density of the transparent polymer powder (B) is preferably 0.10 kg / L to 0.70 kg / L, preferably 0.20 kg / L to 0.60 kg / L, preferably 0.30 kg / L to 0.55 kg / L, and preferably 0.40 kg / L to 0.50 kg / L.

[0043] A-3. Binder (C) As described above, the spherical polymer fine particles (A) and the transparent polymer powder (B) are bound by the binder (C) to form the powder granule. It is preferable to form the powder granule with a small amount of the binder (C). By forming the powder granule with a small amount of the binder (C), it is advantageous in that a powder granule excellent in heat resistance stability and discoloration resistance can be obtained. The shape of the spherical polymer fine particles (A) is one of the causes of a decrease in binding force, but according to the present invention, a powder granule that is favorably bound can be obtained even if the content of the binder is reduced, which is advantageous from the viewpoints of cost, dispersibility, and coloring. The binder (C) is preferably excellent in heat stability (deterioration at the processing temperature of the resin as little as possible) and color stability (resistance to heat discoloration and resistance to light discoloration). As described above, the binder (C) is composed of an aqueous polymer (preferably a colorless and transparent polymer or an aqueous dispersion).

[0044] As described above, the content of the binder (C) is 2 to 30 parts by mass (dry mass) relative to 100 parts by mass of the powder granulated product. The content of the binder (C) is preferably 3 to 25 parts by mass, more preferably 4 to 20 parts by mass, relative to 100 parts by mass of the powder granulated product. If the content is within this range, a powder granulated product having excellent dispersibility and little coloring can be obtained.

[0045] Examples of the aqueous polymer constituting the binder (C) include acrylic resins, polyester resins, polyurethane resins, etc. These resins may be one type or two or more types. By using the above resins, it is possible to obtain a powder granulated product having excellent dispersibility, optical properties, handling properties, and breaking strength.

[0046] The binder (C) includes a polymer having a hydrophilic group (hydrophilic unit) and a hydrophobic group (hydrophobic unit). The polymer binder (C) preferably has a polymer structure capable of binding a powder mixture consisting of component (A) and component (B), and other components as necessary, with a high binding force. That is, the powder that is a component of the powder granulation product may be a hydrophilic powder, a hydrophobic powder, or a mixture of various powders having both properties, so that the polymer binder (C) preferably has a structure of a hydrophilic group and a hydrophobic group in the polymer structure. Specifically, a polymer having a hydrophilic group structure in the polymer structure is, for example, a polymer having an acrylic or methacrylic ester bond structure, an ester bond structure, a urethane bond structure, or an amide bond structure in its structure. An example of the hydrophobic group is a hydrocarbon structure.

[0047] The weight-average molecular weight of the polymer constituting the binder (C) is preferably 10,000 to 500,000, more preferably 20,000 to 300,000, even more preferably 30,000 to 200,000, and particularly preferably 30,000 to 100,000. Within such ranges, a powder granulated product having excellent breaking strength can be obtained. If the weight-average molecular weight is 10,000 or more, the binding force can be further increased. In addition, during the granulation process, the binder (C) is fluidized and easily blends with the surfaces of the powder granulated product constituents, which can be advantageous in increasing the breaking strength of the powder granulated product.

[0048] The softening temperature (glass transition temperature or melting point) of the polymer constituting the binder (C) is preferably −30° C. to 80° C., more preferably −20° C. to 70° C., and further preferably −15° C. to 65° C. Within such a range, a binder (C) having excellent binding strength can be obtained.

[0049] In one embodiment, the polymer constituting the binder (C) is an aqueous polymer (can be used in the form of an aqueous polymer). By using an aqueous polymer, a high binding force can be obtained even for spherical polymer particles that are difficult to bind due to their shape. The aqueous polymer can be used in the form of an aqueous solution or an aqueous dispersion (emulsion or suspension) containing a polymer (preferably with a median diameter (D50) of 1 μm or less). By using such an aqueous polymer, the surface of the powder granule constituent components can be uniformly, thinly, and entirely covered, and a powder granule having excellent breaking strength can be obtained. The details of the method of blending the aqueous polymer liquid will be described later, but it is preferable to blend it little by little with the mixed powder particles of component (A) and component (B) and add it so that it spreads over the entire surface.

[0050] In the above aqueous dispersion, the median diameter (D50) of the aqueous polymer is preferably 0.1 μm to 1 μm, more preferably 0.1 μm to 0.8 μm, even more preferably 0.1 μm to 0.7 μm, and particularly preferably 0.1 μm to 0.5 μm. In one embodiment, the median diameter (D50) of the aqueous polymer is 0.5 μm or less. The average particle diameter of the primary particles is measured using the Coulter counter method. The median diameter (D50) of the aqueous polymer shown here is the particle diameter of the raw material of the powder granulated product, and is the median diameter of the component (C) in the aqueous dispersion. After the powder granules are formed, the aqueous polymer (C) is usually not in a granular form, and the binder (C) is present so as to uniformly and thinly cover the components (A) and (A), between the components (B) and (B), or between the components (A) and (B), thereby binding the components together.

[0051] The refractive index of the binder (C) is preferably 1.46 to 1.59. The refractive index of the binder (C) can be appropriately selected according to the refractive index of the thermoplastic resin to be blended. In addition, when the refractive index of the "polymer binder (C)" according to this embodiment is required to function as a light diffusing agent, it is preferable to match the refractive index of the thermoplastic resin used as the base polymer, for example, around 1.57 for polycarbonate resin and around 1.49 for acrylic resin, and can be appropriately selected.

[0052] The binder (C) may be a commercially available product. The acrylic aqueous dispersion may be appropriately selected from, for example, the "Saibinol (registered trademark)" series of Saiden Chemical Co., Ltd. The polyester aqueous solution may be appropriately selected from, for example, the "Pluscoat (registered trademark)" series of GOO Chemical Co., Ltd. The polyurethane aqueous dispersion may be appropriately selected from, for example, the "Hydorsize (registered trademark)" series of Michaelman Co., Ltd.

[0053] A-4. Other ingredients The powder granules may contain any other suitable powder additives as necessary. Examples of additive powders include antioxidants, light stabilizers, ultraviolet absorbers, heat stabilizers, impact modifiers, antibacterial agents, dispersants, compatibilizers, processing aids, lubricants, coupling agents, hydrolysis inhibitors, and the like. These may be liquid additives. The additive powders are blended in small amounts (usually a few mass % or less).

[0054] In one embodiment, a dispersant may be used as the additive powder (however, dispersants containing phosphorus, nitrogen, sulfur, metals, etc. that may cause coloring and dispersants with poor heat resistance are excluded).

[0055] The dispersant may provide benefits such as improving the productivity (discharge speed) of powder granulated material, reducing frictional heat during granulation, and improving the ease of cleaning the granulation device.

[0056] In one embodiment, the dispersant that can be preferably used is at least one selected from the group consisting of polyhydric alcohol fatty acid ester, polyglycerin fatty acid ester, condensed hydroxy fatty acid, and alcohol ester of condensed hydroxy fatty acid. These dispersants have excellent heat resistance stability in the final resin composition, little retention coloring, can maintain the transparency and molecular weight reduction of the base polymer, and can further suppress heat generation during melt kneading and reduce degradation due to processing, and can exhibit other excellent properties.

[0057] The polyhydric alcohol fatty acid ester is an ester compound composed of a polyhydric alcohol and a fatty acid. Examples of the polyhydric alcohol fatty acid ester include esters of polyhydric alcohols such as pentaerythritol and glycerin and fatty acids having 8 or more carbon atoms (preferably 8 to 24 carbon atoms, more preferably 10 to 22 carbon atoms).

[0058] The polyglycerol fatty acid ester is an ester compound composed of polyglycerol and a fatty acid. Examples of the polyglycerol fatty acid ester include diglycerol palmitate, diglycerol stearate, diglycerol oleate, decaglycerol palmitate, decaglycerol stearate, and decaglycerol oleate.

[0059] The content of the dispersant is usually 0.01% by mass to 10% by mass, preferably 0.1% by mass to 7% by mass, and more preferably 0.3% by mass to 5% by mass, based on the total amount of the powder granulated product.

[0060] B. Manufacturing method of powder granulation The powder granules can be produced by any suitable method, for example, a compressed granule of a mixture containing spherical polymer fine particles (A), transparent polymer powder (B), and a binder (C).

[0061] In one embodiment, the method for producing the powder granulation product includes a mixing step of mixing spherical polymer microparticles (A), transparent polymer powder (B), and a binder (C) to obtain a powder mixture; a granulation step of compressing and granulating the powder mixture to obtain a powder granulation product precursor; and a heating step of heating the powder granulation product precursor.

[0062] In the above mixing step, the spherical polymer fine particles (A) and the transparent polymer powder (B) may be mixed in advance, and then the binder (C) may be further mixed therein.

[0063] In the mixing step, water may be further added. By uniformly dispersing water in small amounts at an appropriate mixing ratio throughout the mixture, granulation in the granulation step can be stabilized, and granules excellent in shape and hardness can be obtained.

[0064] In one embodiment, the binder (C) is mixed in the form of an aqueous solution of a water-based polymer or an aqueous dispersion (emulsion or suspension) containing a water-based polymer (for example, with a median diameter (D50) of 1 μm or less). By using the water-based polymer in this way, the surfaces of the powder granule constituent components (spherical polymer particles (A), transparent polymer powder (B), etc.) can be uniformly, thinly, and entirely covered, thereby making it possible to obtain a powder granule with excellent breaking strength. The water-based polymer liquid is preferably added in small amounts to the mixture of the spherical polymer particles (A) and transparent polymer powder (B) so as to be spread over the entire mixture.

[0065] In one embodiment, the binder (C) may be gradually added in the form of, for example, a spray, a shower, or a drip using a nozzle. Here, the spray refers to a state in which a liquid pressurized by a gas such as compressed air is suddenly ejected from a fine hole of a nozzle to form fine particles of the liquid. In addition, the shower refers to a state in which a fluid applied with the same pressure is dispersed and ejected from a shower head (a jig with multiple holes of the same size). The water to be added is not particularly limited, and for example, tap water, distilled water, ion-exchanged water, hard water, soft water, etc. may be used. If necessary, water may be used in combination with other components such as alcohol to improve wettability to the powder raw material. In addition, when other components (for example, solid components) are added, the components may be mixed with the mixture.

[0066] In the above mixing step, it is preferable to mix uniformly using any suitable mixer. Examples of the mixer include a Henschel mixer, a powder kneader (KDH, KDA, CKD, CPM) (Dalton), a Spartan mixer (SPM) (Dalton), and an SP granulator (SPG) (Dalton). From the viewpoint of a preferable mixture with excellent granulation properties, when using a Henschel mixer type mixer, it is preferable to use a combination of upper and lower blades, with the upper blade being a Y1 blade (trade name, manufactured by Nippon Coke and Engineering Co., Ltd.) and the lower blade being an S0 blade (trade name, manufactured by Nippon Coke and Engineering Co., Ltd.). It is also preferable to install a deflector in the stirring tank and mix. That is, by making it possible to uniformly disperse each component throughout the mixture in the mixing step, it is possible to increase the productivity and quality stability in the granulation step and obtain granules with excellent shape and granule hardness.

[0067] The mixing time in the mixing step can be any appropriate mixing time depending on the type of components, the type of mixer, the component blending ratio, etc. Preferably, the mixing time is set so that the surfaces of components (A) and (B) are sufficiently and uniformly covered with the binder (component (C)). A high-speed mixer such as a Henschel mixer or a Spartan mixer can perform the mixing for 1 to 10 minutes. On the other hand, a powder kneader may require a processing time of several minutes to 60 minutes.

[0068] The amount of water blended in the mixing step can be any appropriate amount depending on the properties of the powder (water absorption, etc.). The amount of water blended in the mixing step is, for example, 5 parts by mass to 100 parts by mass, preferably 8 parts by mass to 70 parts by mass, relative to 100 parts by mass of the total amount of the powder mixture of the spherical polymer fine particle powder (A) and the transparent polymer powder (B). If it is within such a range, it can be advantageous in producing a powder granulated product precursor having excellent granulation properties uniformly and at a high granulation production rate in the granulation step while suppressing excessive heat generation. Blending a small amount of water is preferable in terms of reducing the amount of carbon dioxide generated, since it can reduce the amount of energy required in the drying step.

[0069] The time for adding water in the mixing step is, for example, 1 to 60 minutes, preferably 3 to 30 minutes, and more preferably 5 to 20 minutes.

[0070] In the above granulation step, a semi-wet granulation method can be adopted as the compression granulation method. Examples of the compression granulation method / semi-wet granulation method include a disk pelleter method, a tableting method, and a briquetting method. From the viewpoint of the balance between productivity and the quality of the obtained powder granulated product, the disk pelleter method is preferably adopted. More specifically, the disk pelleter method includes a roller disk die method, a roller ring die method, a double die method, and a flat die method. As a commercially available disk pelleter type granulator, for example, the disk pelleter F series manufactured by Dalton can be mentioned.

[0071] The disk pelletizer has a disk plate having a large number of holes of, for example, 1 mm to 30 mm, and a roller for pressure-feeding the raw material into the holes of the disk plate. The raw material (powder mixture containing moisture) supplied between the disk plate and the roller is pressed into the holes of the disk as the roller rotates, and an extrudate having a substantially cylindrical or rectangular column shape is formed. The extruded powder granulation precursor is cut by a cutter or the like on the back side of the disk to obtain a pellet-shaped powder granulation product. The length of the powder granulation precursor can be adjusted by the distance between the back side of the disk and the cutter and the number of rotations of the roller. The distance between the disk plate and the cutter can be any appropriate distance depending on the type of powder raw material, etc. The distance between the disk plate and the cutter is, for example, 1 mm to 30 mm, more preferably 2 mm to 20 mm, and even more preferably 3 mm to 10 mm.

[0072] In the heating step, moisture is removed from the powder granule precursor, and the binding strength of the powder granule precursor can be increased by the heating step.

[0073] Any appropriate method can be adopted as the heating method in the heating step. As described above, in the heating step, the binding of the powder granulated product is promoted. The heating temperature is, for example, 50°C to 200°C, preferably 80°C to 180°C, and more preferably 100°C to 150°C.

[0074] In one embodiment, the heating temperature in the heating step is equal to or higher than the softening temperature of the binder (C). Here, the softening temperature refers to the glass transition temperature or the melting point. The difference between the heating temperature in the heating step and the softening temperature of the binder (C) is, for example, 1°C to 100°C, preferably 10°C to 80°C, and more preferably 20°C to 60°C.

[0075] In the heating step, any suitable heating (drying) equipment is used. For example, a vibration fluidized dryer is preferable because it can perform drying efficiently in a short time, and examples thereof include the vibration fluidized dryer VDF series manufactured by Dalton. After the heating step, a powder granulated product from which fine powder has been removed can be obtained by treating with a vibration sieve or the like.

[0076] Compared with the conventional method of obtaining a master batch by melt blending through a melt kneading device such as a twin screw extruder, the powder granulation according to the embodiment of the present invention can control the concentration of the spherical polymer fine particles (A) over a wide range, and can obtain a powder granulation continuously at a high production rate. Furthermore, compared with the melt kneading method such as a twin screw extruder, the total amount of electricity used to obtain the granulation can be greatly reduced. The packaging cost and transportation cost of the high concentration granulation can be greatly reduced.

[0077] C. Melt compounding of powder granulation In one embodiment, the powder granules are used as a raw material for a thermoplastic resin compound. Also, a melt compound of the powder granules and a thermoplastic resin (a thermoplastic resin to which the powder granules are applied) is provided. Any thermoplastic resin is used as the thermoplastic resin. Examples of the thermoplastic resin include styrene-based resins, acrylic-based resins, styrene-methacrylate-based resins, polycarbonate-based resins, and alicyclic polyolefin-based resins. The thermoplastic resin is preferably a transparent resin.

[0078] The ratio (nP / nB) of the refractive index nB of the transparent polymer powder (B) to the refractive index nP of the thermoplastic resin to which the powder granules are applied is preferably 0.8 to 1.2, more preferably 0.85 to 1.15, even more preferably 0.9 to 1.1, and particularly preferably 0.95 to 1.05. In one embodiment, the transparent polymer powder (B) may be the same type as the thermoplastic resin to which the powder granules are applied, and nP / nB may be 1.

[0079] Any suitable method can be used as a method for producing the molten compound. For example, a kneader, a Banbury mixer, a roll, or a single-screw or multi-screw extruder having two or more screws can be used. A twin-screw extruder is preferably used. The composition obtained by melt kneading is pelletized.

[0080] By using the above powder granulation product as a master batch, it is possible to provide a melt compound that can produce a resin composition containing spherical polymer microparticles at various desired concentrations with high precision, high productivity, and stability, while also increasing safety against dust explosions and allowing the compound to be produced in a good working environment. The quality of the resulting resin composition can also exhibit good dispersibility of the spherical polymer microparticles, good color tone, and good optical properties (light diffusion and transparency). In one embodiment, the above powder granulation product can be directly charged as a master batch into a resin processing device such as an injection molding machine or an extrusion molding machine to obtain various resin composition molded products. EXAMPLES

[0081] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In addition, parts and % are based on mass unless otherwise specified.

[0082] [Example 1] Production of powder granulated material FM Mixer (manufactured by Nippon Coke & Engineering Co., Ltd., product name "5FM5C / I"; processing volume: 5L) 75 parts by mass of spherical polymer microparticles A-1 (polymethylsilsesquioxane-based crosslinked particles, manufactured by Aica Kogyo Co., Ltd., product name "Ganzpearl SI-020") and 25 parts by mass of transparent polymer powder B-1 (manufactured by Asahi Kasei Corporation, product name "Delpowder 60N") were added to the mixture, and the mixture was stirred for 2 minutes with the stirring blade rotating at 1,000 rpm to obtain a powder mixture. The FM mixer had a combination of upper and lower blades, with the upper blade being a Y1 blade (product name, manufactured by Nippon Coke and Boiler Co., Ltd.) and the lower blade being an S0 blade (product name, manufactured by Nippon Coke and Boiler Co., Ltd.) A baffle plate was also installed in the mixing vessel. While rotating the stirring blade at 2,000 rpm, a mixture of 15 parts by mass of binder C-1 (manufactured by Saiden Chemical Industry Co., Ltd., product name "Saibinol CA-200", acrylic resin-based aqueous dispersion, median diameter (D50): 0.12 μm, solid content concentration: 49%) and 10 parts by mass of tap water was added to 100 parts by mass of the above powder mixture, and stirred for 15 minutes to obtain a powder mixture to which the binder had been added. The temperature of the powder mixture was 50°C. This powder mixture was charged into a disc pelleter (manufactured by Dalton, product name "Disc Pelleter F-5 / 11-175") to obtain a pellet-shaped granulated material precursor. In this case, the diameter of the die hole was 3 mm, the thickness of the die plate was 15 mm, the effective length of the die hole was 10 mm, and the rotation speed of the roller of the dispelleter was 108 rpm. The obtained granulated product precursor was dried at 100°C for 6 hours using a hot air circulation type dryer to obtain a granulated product (PG-1). The powder granulated product had a bulk density of 0.47 kg / L, a moisture content of 0.28 mass%, and a granulated product breaking strength of 1.0 kg, and was a powder granulated product with excellent handleability. A photograph of the appearance of the obtained powder granulated product (PG-1) is shown in Figure 1. A cross-sectional photograph of the obtained powder granulated product (PG-1) is shown in Figure 2.

[0083] [Examples 2 to 5, Comparative Examples 1 to 6] A powder granulated product was obtained in the same manner as in Example 1, except that the spherical polymer particles, transparent polymer powder, and binder shown in Table 1 and below were used in the blending amounts shown in Table 2. In addition, Comparative Example 1 is an example using only spherical polymer fine particles "A-1", but granulation was not possible. Comparative Example 2 is an example in which the binder C-1 was omitted compared to Example 1, but granulation was not possible. Comparative Example 3 is a result of using "C-3" which does not meet the requirements of the present application as the binder, but the breaking strength was significantly inferior. Comparative Example 4 is an example in which the spherical polymer fine particles "A-1" were granulated without the transparent polymer powder (B-1), but granulation was not possible due to clogging of the die. Comparative Example 5 is an example in which the binder (C-2) was omitted compared to Example 5, but the breaking strength was significantly inferior. Comparative Example 6 is an example in which the amount of binder (C-2) was 1.2 mass% (outside the range of the present invention), but the breaking strength was significantly inferior and insufficient.

[0084] [Comparative Example 7] Production and evaluation of high-concentration spherical polymer master batch by melt kneading 70 parts by mass of spherical polymer particles "Ganzpearl SI-020 (A-1 in Table 1)" and 30 parts by mass of transparent polymer powder B-1 (manufactured by Asahi Kasei Corporation, product name "Delpowder 60N") were premixed by hand shaking, and the mixture was fed through a hopper attached to the most upstream part of an 18 mm twin-screw extruder (manufactured by Shibaura Machine Co., Ltd., model "TEM18-SS, L / D=50") and continuously melt-kneaded. The cylinder temperature of the extruder was set to 150°C just below the hopper, and gradually increased to 230°C up to the middle stage, and was kept at 230°C from the middle stage onwards. The screw rotation speed of the extruder was 100 rpm. Although melt-kneading was started with a low feed rate of 1 to 2 kg / hr of raw materials, the extruder was overloaded immediately after feeding, and continuous melt-kneading was impossible. In other words, a melt-kneaded granule containing 70% by mass of crosslinked spherical polymer particles could not be obtained.

[0085] [Table 1] Component (A): spherical polymer particles (A-1) "Ganzpearl SI-020 (product name)" manufactured by AICA Kogyo Co., Ltd. (polymethylsilsesquioxane-based crosslinked particles, median diameter (D50): 2.0 μm, bulk density: 0.4 kg / L, refractive index: 1.41, sphericity: 1.02, angle of repose: 30°) (A-2) "Techpolymer MBX-8 (trade name)" manufactured by Sekisui Chemical Co., Ltd. (methyl methacrylate polymer-based crosslinked particles, median diameter (D50): 8.0 μm, bulk density: 0.6 kg / L, refractive index: 1.49, sphericity: 1.00, angle of repose: 20°) (A-3) "Techpolymer MBX-5 (product name)" manufactured by Sekisui Chemical Co., Ltd. (methyl methacrylate polymer-based crosslinked particles, median diameter (D50): 5.0 μm, bulk density: 0.5 kg / L, refractive index: 1.49, sphericity: 0.99, angle of repose: 15°) Component (B): Transparent polymer powder (B-1) "Delpowder 60N (trade name)" manufactured by Asahi Kasei Corporation (polymethyl methacrylate granules, median diameter (D50): 200 μm, bulk density: 0.85, refractive index: 1.49, softening temperature: 90° C. (Vicat softening point) (B-2) "YS Resin SX-100 (product name)" manufactured by Yasuhara Chemical Co., Ltd. (polystyrene granular material, median diameter (D50): 300 μm (ground using an FM mixer), bulk density: 0.60, refractive index: 1.59, softening temperature: 62°C (measured by DSC, glass transition temperature) Component (C): Binder (C) (C-1) "Saibinol CA-200 (trade name)" manufactured by Saiden Chemical Co., Ltd. (acrylic resin-based aqueous dispersion, median diameter (D50): 0.12 μm, solid content concentration: 49%, softening point (glass transition point): -10°C) (C-2) "Pluscoat Z-561 (trade name)" manufactured by GOO Chemical Industry Co., Ltd. (water-soluble polyester, solid content: 25%, refractive index: 1.57, molecular weight: about 27,000) (C-3) "CHEMIPEARL A100 (product name)" manufactured by Mitsui Chemicals, Inc. (water-soluble polyolefin dispersion, solid content concentration: 40%, median diameter (D50): 4 μm (used in Comparative Example 3)

[0086] [Table 2]

[0087] <Evaluation> The obtained powder granules were subjected to the following evaluations, and the results are shown in Table 3. (1) Granulation property (possibility of granulation) The obtained powder granulated product was confirmed, and the granulation properties were evaluated according to the following criteria. Good: Powder granules with diameters of 2.8 to 3.5 mm are obtained. ×: The powder raw material does not have binding properties, and powder granules cannot be obtained. Or, granules cannot be obtained stably due to clogging of the die. The granulation process temperature was measured by measuring the temperature of the granules immediately after granulation using a thermocouple. (2) Granulation speed The production rate of powder granules per hour (kg / Hr) was calculated. (3) Bulk density The dried powder granules were allowed to fall naturally into a 1-liter measure, filled to the brim, and weighed to exactly 1 liter in volume. The mass was then measured to calculate the bulk density of the powder granules (unit: kg / L). (4) Granule (pellet) size 25 grains of the powder granules were taken out, and the length and diameter of the granules were measured using a caliper, taking the average value of the 25 grains. (5) Moisture content The amount of moisture (unit: mass%) remaining in the powder granules was measured using an infrared moisture meter (FD-660 manufactured by Kett Electric Laboratory). (6) Breaking strength The breaking strength (unit: kg) of the powder granules was measured using a Kiya hardness tester (manufactured by Shiro Sangyo Co., Ltd., product name "WPF1600-B"). The measured value was the average value of 25 grains of the powder granules. (7)Angle of repose The angle of repose (°) was measured using a repose angle measuring instrument (manufactured by AS ONE Corporation, product name "Angle of Repose Measuring Instrument").

[0088] [Table 3]

[0089] [Reference Example 6] Production and evaluation of reference resin composition One part by mass of spherical polymer particles "Ganzpearl SI-020 (A-1 in Table 1)" and 99 parts by mass of acrylic resin pellets (Asahi Kasei Corporation's "Delpet 60N") were premixed by hand shaking, and the mixture was fed through a hopper attached to the most upstream part of a 40 mm single screw extruder (Isuzu Kakoki Co., Ltd., model "SV-40-32-EXT", L / D = 32, with a dulmage tip) and melt-kneaded continuously. The cylinder temperature of the extruder was set to 150°C just below the hopper, and gradually increased to 230°C up to the middle stage, and was set to 230°C from the middle stage onwards. The screw rotation speed of the extruder was set to 100 rpm. The molten mixture was continuously extruded in the form of a strand and cooled in a strand bath (water temperature: 40° C.) to produce pellets having a diameter of 3 mm and an average length of 3 mm. In Reference Example 6, since separation of the spherical polymer particles (A-1) and the acrylic resin pellets occurred during long-term operation, the pellets were homogenized by a post-blending treatment after pelletization. The acrylic resin composition of the resin composition (containing 1% by mass of A-1) was placed in an injection molding machine (manufactured by Toyo Machinery & Metals, product name "Si-80IV"), and a business card-sized molded body in the shape of a three-tiered plate (80 mm x 50 mm x 1, 2, and 3 mm thick) was obtained at a cylinder setting temperature of 230°C, a mold temperature of 60°C, and a cooling time of 15 seconds. The total light transmittance (%), parallel transmittance (%), diffuse transmittance (%), and haze (%) were measured for the obtained molded body at a thickness of 1 mm using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH5000"). In addition, for the same molded body, a color difference meter (manufactured by Konica Minolta, Inc., product name "CM-3600d") was used to measure the L * , a * , b * , and numerical measurements were carried out for each. The "color / optical properties" in Table 4 were evaluated according to the following criteria, based on the results shown in Reference Example 6. Good: ΔE value is less than 0.7 ×: ΔE value exceeds 0.7 Moreover, "dispersion" in Table 4 is the result of visually observing the dispersibility of the spherical polymer particles at a location 1 mm deep in the molded product, and was evaluated according to the following criteria. ◯: Dispersion is good, and no agglomerates of spherical polymer particles are observed. ×: Aggregates of spherical polymer particles are present.

[0090] [Example 7] Production and evaluation of resin composition using "powder granules" 1.45 parts by mass of the powder granulation product (PG-1) obtained in Example 1 and 98.55 parts by mass of acrylic resin pellets (Asahi Kasei Corporation's "Delpet 60N") (not powder B-1) were premixed by hand shaking, and the composition was adjusted so that the composition concentration of "Ganzpearl SI-020 (A-1)" in the final composition was 1 mass%, the same as in "Reference Example 6." Melt kneading was performed in the same manner as in Reference Example 6 to produce pellets of the resin composition. In Example 7, stable kneading and discharge speed were obtained, and production stability was extremely excellent. That is, in Example 7, even during long-term operation, separation of the spherical polymer particles (A-1) and the acrylic resin pellets "Delpet 60N" did not occur, and a resin composition with a stable composition could be continuously obtained, so that post-blending treatment after pelletization was not necessary. From the obtained pellets of the resin composition, an injection molded article was produced in the same manner as in Reference Example 6, and the optical properties and dispersibility were evaluated. As a result, as shown in Table 4, the same results as in Reference Example 6 were obtained.

[0091] [Example 8] Melt kneading was carried out in the same manner as in Example 7 to prepare pellets of a resin composition, except that the powder granule "PG-3" obtained in Example 3 was used instead. In Example 8, stable kneading and discharge speed were obtained, and production stability was extremely excellent. In Example 8, as in Example 7, separation of the spherical polymer particles (A-1) and the acrylic resin pellets did not occur even during long-term operation, and a resin composition with a stable composition could be continuously obtained, so that post-blending treatment after pelletization was not necessary. From the obtained pellets of the resin composition, an injection molded article was produced in the same manner as in Reference Example 6, and the optical properties and dispersibility were evaluated. As a result, as shown in Table 4, the same results as in Reference Example 6 were obtained.

[0092] [Table 4]

[0093] [Reference Example 9] Production and evaluation of reference resin composition One part by mass of spherical polymer particles "Techpolymer MBX-8 (A-2 in Table 1)" and 99 parts by mass of polycarbonate resin pellets (manufactured by Covestro under the trade name "Makrolon 2400") were premixed by hand shaking, and the mixture was fed into the same 40 mm single screw extruder as in Reference Example 6 through a hopper attached to the most upstream portion, and continuously melt-kneaded. The cylinder temperature of the extruder was set to 230°C just below the hopper, and gradually increased to 280°C up to the middle portion, with the middle portion and thereafter being set to 280°C. The screw rotation speed of the extruder was set to 100 rpm. The molten mixture was continuously extruded in the form of a strand and cooled in a strand bath (water temperature: 40° C.) to produce pellets having a diameter of 3 mm and an average length of 3 mm. In addition, in Reference Example 9, similar to Reference Example 6, separation of the spherical polymer microparticles (A-2) and the polycarbonate resin pellets occurred during long-term operation, so after pelletization, the pellets were homogenized by a post-blending process. The polycarbonate resin composition of this resin composition (containing 1% by mass of A-2) was used in the same injection molding machine as in Reference Example 6 to produce a business card-sized three-tiered plate-shaped molded body with a cylinder setting temperature of 280°C, a mold temperature of 80°C, and a cooling time of 15 seconds. The optical properties and dispersibility were evaluated in the same manner as in Reference Example 6. The "color / optical properties" in Table 5 are based on Reference Example 9.

[0094] [Example 10] Production and evaluation of resin composition using powder granules 1.43 parts by mass of the powder granulation product "PG-4" obtained in Example 4 and 98.57 parts by mass of the polycarbonate resin pellets used in Reference Example 9 ("Makrolon 2400" manufactured by Covestro) were premixed by hand shaking, and the composition was adjusted so that the composition concentration of "Techpolymer MBX-8 (A-2)" in the final composition was 1% by mass, the same as in Reference Example 9. Melt kneading was performed in the same manner as in Reference Example 9 to produce pellets of the resin composition. In Example 10, stable kneading and discharge speed were obtained, and production stability was extremely excellent. That is, in Example 10, since a resin composition with a stable composition could be obtained continuously even during a long operation, post-blending treatment after pelletization was not necessary. From the obtained pellets of the resin composition, an injection molded article was produced in the same manner as in Reference Example 9, and the optical properties and dispersibility were evaluated. As a result, as shown in Table 5, the same results as in Reference Example 9 were obtained.

[0095] [Table 5]

Claims

1. A powder granulation product comprising spherical polymer fine particles (A), a transparent polymer powder (B), and a binder (C), the content of the spherical polymer fine particles (A) is 10 parts by mass to 97 parts by mass based on 100 parts by mass of the powder granules, the content of the transparent polymer powder (B) is 1 part by mass to 88 parts by mass based on 100 parts by mass of the powder granules, The content of the binder (C) is 2 parts by mass to 30 parts by mass (dry mass) relative to 100 parts by mass of the powder granules, the spherical polymer fine particles (A) contain a crosslinked resin, The transparent polymer powder (B) has a softening temperature of 50° C. or higher, the material constituting the transparent polymer powder (B) is at least one selected from the group consisting of a styrene-based resin, an acrylic-based resin, a styrene-methacrylate-based resin, a polycarbonate-based resin, a polyester-based resin, a polyurethane-based resin, a petroleum resin, a terpene-based resin, and an alicyclic polyolefin-based resin; The binder (C) contains a water-based polymer, The aqueous polymer has a hydrophilic group and a hydrophobic group. Powder granules.

2. The powder granule according to claim 1, wherein the material constituting the spherical polymer fine particles (A) is at least one selected from the group consisting of crosslinked acrylic resins, crosslinked styrene resins, crosslinked acrylic-styrene resins, crosslinked silicone resins, crosslinked silicone-acrylic resins, melamine resins, and benzoguanamine resins.

3. 2. The powder granulated product according to claim 1, wherein the ratio (b / a) of the minor axis b of the spherical polymer fine particles (A) to the major axis a of the spherical polymer fine particles (A) is 0.9 or more.

4. The powder granulated product according to claim 1, wherein the median diameter (D50) of the spherical polymer fine particles (A) is 0.1 μm to 300 μm.

5. 2. The powder granulation product according to claim 1, wherein the spherical polymer fine particles (A) have a bulk density of 0.05 kg / L to 1.0 kg / L.

6. The powder granulation product according to claim 1, wherein the refractive index of the spherical polymer fine particles (A) is 1.40 to 1.

70.

7. The powder granule according to claim 1, wherein the transparent polymer powder (B) has a median diameter (D50) of 1 μm to 3000 μm.

8. The powder granule according to claim 1, wherein the refractive index of the transparent polymer powder (B) is 1.45 to 1.

65.

9. The powder granule according to claim 1, wherein the transparent polymer powder (B) has a bulk density of 0.10 kg / L to 0.70 kg / L.

10. The powder granulated product according to claim 1, wherein the aqueous polymer has a median diameter (D50) of 0.5 μm or less.

11. 2. The powder granulated product according to claim 1, wherein the aqueous polymer is at least one selected from the group consisting of an acrylic resin, a polyester resin, and a polyurethane resin.

12. The powder granulated product according to claim 1, having a breaking stress of 0.3 kg or more when measured with a Kiya hardness tester.

13. The powder granulated product according to claim 1, having a bulk density of 0.3 kg / L to 1.0 kg / L.

14. The powder granulated product according to claim 1, having a median diameter (D50) of 1 mm to 10 mm.

15. The powder granulated product according to claim 1 , which has a substantially cylindrical or substantially prismatic shape.

16. a mixing step of mixing the spherical polymer fine particles (A), the transparent polymer powder (B), and the binder (C) to obtain a powder mixture; A granulation step of compressing and granulating the powder mixture to obtain a powder granulation precursor; and A heating step of heating the powder granulated product precursor; A method for producing the powder granulated product according to any one of claims 1 to 15.

17. The method for producing a powder granulated product according to claim 16, wherein in the granulation step, the compression granulation method is a disk pelletizer method.

18. The binder (C) contains a water-based polymer, The mixing step includes adding an aqueous solution containing a water-based polymer or an aqueous dispersion containing a water-based polymer. A method for producing the powder granulated product according to claim 16.

19. Use of the powder granule according to any one of claims 1 to 15 as a raw material for a compound containing a thermoplastic resin or as a molding material.

20. Use of the powder granules according to claim 19 as a raw material for a thermoplastic resin compound containing, as a thermoplastic resin, one or more resins selected from the group consisting of styrene-based resins, acrylic-based resins, styrene-methacrylate-based resins, polycarbonate-based resins and alicyclic polyolefin-based resins.

21. The use of the powder granule according to claim 19, wherein the ratio (nP / nB) of the refractive index nB of the transparent polymer powder (B) to the refractive index nP of the thermoplastic resin is 0.8 to 1.2.

Citation Information

Patent Citations

  • Propylene polymer composition

    JP1987215646A

  • Polypropylene resin composition and film prepared therefrom

    JP1995179678A

  • Thermoplastic polymer granule and method for producing thermoplastic polymer granule

    JP2023011323A

  • Filler granulated substance

    JP2023032658A

  • Powder granule, method for producing powder granule and use thereof

    JP2023163778A